PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING MENGGUNAKAN MOODLE KELAS X SEMESTER GENAP - Ika Sundari; Nurfajriani Nurfajriani; Marini Damanik (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
This stuy aims to develop e-modules for class X high school student and to obtain innovative e-modules for even semester of class X high school students. The research method develop (R&D) using the ADDIE floating model. The subject and location of this research in class X SMA Swasta Harapan is located in Langkat. The instrument used in the BNSP instrument with four criteria namely content feasibility,language,graphic and presentation. The BNSP instrument is used to determine the suitability of the e-module that has been developed is assessed as a validator expert. From the result of the e-module validator based on discovery learning using moodle class X even semester,totality value is 4,20 with a valid category without revision. After the e-module was developed , it wa obtained average very suitable for use of 3,86 category very suitable for use in class X even semester Keyword: Development, E-modul,Discovery Learning, Moodle